Obligations in Contract, Tort and Equity: Reliance, Responsibility, and the Moral Dimension: Essay in honour of Sir John McGrath - Tipping, Andrew (Victoria University of Wellington Law Review, 2021)
I publish this essay to honour the memory of Sir John McGrath. I sat with Sir John for a number of years, first in the Court of Appeal and then in the Supreme Court. Professional respect soon turned into friendship. While we did not always agree, I always respected his views. They were carefully considered and fully researched. John gave detailed consideration to the opinions of others but was very much his own man when it came to his ultimate conclusion. His innate caution in departing from the well-trodden path was a valuable contribution in a final appellate court. Stability is an important feature of any legal system. And John provided that quality, but not at the expense of innovation when that was clearly desirable and could be achieved in a principled way. John’s passing, so soon after his retirement, was a great loss, not only to his wife and family, but also to his many friends and colleagues, both in the law and beyond.